Evaluation of Infection Prevention and Control Program Management at Brawijaya Level III Hospital - Sulistyowati, Eni; Mahendra, Guntur; Zubaidah, Miftakhul; -, Chamariyah (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2024)
The Infection Prevention and Control (IPC) program is a crucial component in improving the quality of healthcare services and patient safety. This article aims to evaluate the management of the IPC program at Brawijaya Level III Hospital, identify challenges faced in program implementation, and develop strategies that can be adopted to improve program effectiveness. The research method used was a descriptive evaluation with a qualitative approach, involving in-depth interviews with healthcare workers and analysis of relevant documents. The results indicate that the roles and responsibilities of the IPC Committee members are well-defined, and they are responsible for developing IPC policies, monitoring, and routinely evaluating the implementation of infection prevention procedures. However, several units, such as the ICU and Mortuary, have low levels of compliance with the use of Personal Protective Equipment (PPE) (around 71%). The main challenges in implementing the IPC program include limited human resources, lack of infrastructure support, and inconsistencies in adherence to standard procedures. Proposed strategies to address these challenges include improving healthcare worker training, optimizing the use of technology, and strengthening cross-departmental collaboration. With the right strategy, it is hoped that PPI management at Brawijaya Level III Hospital can contribute to improving the quality of health services.